Correlation between Anthropometry and Fat Caliper Measurements with Triglyceride Ratios and Blood Pressure: Korelasi antara Pengukuran Antropometri dan Pengukuran Kaliper Lemak dengan Rasio Trigliserida dan Tekanan Darah - Limanan, David; Santoso, Alexander; Teguh, Stanislas; Jap, Ayleen (Jurnal Keperawatan Bunda Delima, 2025)
Introduction: Anthropometric measurements, such as fat calipers and circumference, offer non-invasive insights into fat distribution and total adiposity, both crucial health markers. Increased visceral fat heightens cardiovascular risk by driving metabolic dysfunction. The TG/HDL-C ratio serves as a strong predictor of cardiovascular risk, linking systemic inflammation, dyslipidemia, and insulin resistance. Excess adiposity also elevates blood pressure by impairing lipid metabolism and vascular function. This study aims to see the correlation between anthropometry measurement (calf, neck, upper arm, and waist circumferences), body weight, body mass index and fat caliper with the triglyceride/HDL ratio and blood pressure. Methods: This cross-sectional study, conducted in Krendang Village in November 2024, included participants aged 18 years or older, excluding those using antihypertensive or cholesterol-lowering medications or unwilling to provide blood samples or undergo physical exams. Measurements included skinfold thickness at four sites, various anthropometric parameters, blood pressure, and venous blood samples analyzed for HDL, triglycerides, and their ratio. Statistical analysis utilized Spearman Correlation, focusing on the triglyceride/HDL ratio Results: Multivariate analysis revealed that waist circumference is the strongest predictor of the triglyceride/HDL ratio. Hip circumference and calf circumference were identified as key indicators for predicting both systolic and diastolic blood pressure, while suprailiac fat caliper and scapular fat caliper were specifically associated with predicting diastolic blood pressure.Conclusion:  Waist circumference, along with select anthropometric and fat caliper measurements, serves as valuable predictors for cardiovascular and metabolic risk factors, emphasizing their importance in early risk assessment.